Puppet Beton Story Berbantuan Gawai untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa - Sulistya Rosid, Dian Perdana (Jurnal Didaktika Pendidikan Dasar, 2018)
The research objectives were to improve children’s learning activities and outcomes through puppet BETON story scaffolded with gadget. A classroom research was conducted at the fifth grade children at Public Elementary School 2 Tarubatang, District of Boyolali in semester II academic year 2016/2017. Learning was initiated with information on media and they continued telling incidence around proclamation of the Indonesia Republic.  Data were analyzed descriptively and qualitatively.  Analysis results show that children’s most active efforts are evident in observation and communication of contents. Moreover, children’s learning outcomes improved to a mean score 80.76 with minimum mastery level 86.6%.